Gerakan Kolaboratif Mahasiswa untuk Semangat Ekologis dan Kebersihan Kampus: Penelitian - Az-Zahro, Aulia Salsabillah (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2026)
This activity originated from the low level of student concern for campus cleanliness and environmental conditions. The main goal of this movement is to foster environmental awareness while building a sustainable culture of cleanliness. The implementation of the activity uses the Asset Based Community Development (ABCD) approach, namely by utilizing and enhancing existing potentials. Concrete forms of the activity include collective clean-up work, planting ornamental and medicinal plants, building goat pens and maintaining catfish, as well as installing small fences as boundaries between areas. The results can be seen from the increased student participation in maintaining cleanliness, the creation of a neat and organized campus environment, and the growing awareness that cleanliness is a shared responsibility. This activity proves that change can begin with small steps carried out in unity. With the spirit of collaboration, support from the campus, and the creation of a comfortable, healthy, and inspiring learning space, this movement is expected to become a real example of the sustainability of a clean culture in educational environments.